Neutrophils from Patients with Primary Ciliary Dyskinesia Display Reduced Chemotaxis to CXCR2 Ligands - Cockx, Maaike; Gouwy, Mieke; Godding, Véronique; De Boeck, Kris; Van Damme, Jo; Boon, Mieke; Struyf, Sofie (Frontiers in Immunology, 2017)
Primary ciliary dyskinesia, cystic fibrosis and chronic obstructive airway disease are characterized by neutrophilic inflammation in the lungs. In cystic fibrosis and chronic obstructive airway disease, improper functioning of neutrophils has been demonstrated. We hypothesized that the pulmonary damage in PCD might be aggravated by abnormal functioning neutrophils either as a primary consequence of the PCD mutation or secondary to chronic inflammation. We analyzed chemotactic responses and chemoattractant receptor expression profiles of peripheral blood neutrophils from 36 patients with PCD, 21 healthy children and 19 healthy adults. We stimulated peripheral blood monocytes from patients and healthy controls and measured CXCL8 and IL-1beta production with ELISA. PCD neutrophils displayed reduced migration towards CXCR2 ligands (CXCL5, CXCL8) in the shape change, microchamber and microslide chemotaxis assays, whereas LTB4 and C5a chemotactic responses were not significantly different. The reduced response to CXCL8 was observed in all subgroups of patients with PCD (displaying either normal ultrastructure, dynein abnormalities or central pair deficiencies) and correlated with lung function. CXCR2 was downregulated in about 65% of the PCD patients, suggestive for additional mechanisms causing CXCR2 impairment. After treatment with the TLR ligands lipopolysaccharide and peptidoglycan, PCD monocytes produced more CXCL8 and IL-1beta compared to controls. Moreover, PCD monocytes also responded stronger to IL-1beta stimulation in terms of CXCL8 production. In conclusion, we revealed a potential link between CXCR2 and its ligand CXCL8 and the pathogenesis of PCD.